Cultural Safety and Leadership Education Program Transformative For Pediatric Nurse at H. Sahudin Regional General Hospital Kutacane - Yusnaini Yusnaini; Ade Kartika; Nandara Priyanti Elna (Abdimas Paspama, 2023)
The implementation of cultural safety and transformative leadership in pediatric nursing care is especially vital in multicultural settings. Pediatric nurses face communication and decision-making challenges influenced by the cultural values of patients' families. However, understanding and applying the principles of cultural safety and transformative leadership practices in pediatric nursing units remains limited. This community engagement program aims to enhance the capacity of pediatric nurses in applying these principles through education, training, and mentoring. The program included a preparation phase, a two-day interactive workshop, two weeks of field mentoring, and evaluation through pre- and post-tests, as well as daily reflections. A total of 20 pediatric nurses participated in the entire series of activities. Evaluation results showed a significant improvement in participants' understanding; the average score for cultural safety increased from 62.3 to 84.1, and for transformative leadership from 58.7 to 81.5. Moreover, participants demonstrated more reflective and inclusive behavior in nursing practice and team leadership. This program proved effective in improving pediatric nurses' knowledge and skills related to cultural safety and transformative leadership. Therefore, it is recommended that the hospital continue the training regularly and expand it to other units to improve the quality of culturally sensitive nursing care